MAINTENANCE THERAPY WITH RITUXIMAB IN ADULT PATIENTS WITH IMMUNE THROMBOCYTOPENIA - Pavkovic M; Trpkovska-Terzieva S; Sotirova T; Cevreska L; Stojanovic A (My University, 2013)
Immune thrombocytopenia (ITP) is an autoimmune disease of unknown etiology, characterized by isolated thrombocytopenia and the absence of any underlying cause for thrombocytopenia. Corticosteroids are the standard first line treatment for patients with symptomatic disease, inducing platelet count recovery in 70-80% of patients; but in many cases, steroid tapering or withdrawal is followed by a decrease of platelet count and the need for additional treatment. Splenectomy is still the standard salvage therapy in cases refractory to corticosteroid therapy. In the past decade monoclonal anti-CD20 antibodies (Rituximab) are being increasingly used in patients with refractory ITP and other autoimmune diseases. Recent studies show that Rituximab is useful in the treatment of patients with chronic and refractory ITP. We report two cases with chronic ITP treated with standard dose of Rituximab in four weekly doses and than continue to receive maintenance therapy with Rituximab for 2 years.
Keywords: imune thrombocytopenic purpura; monoclonal anti-CD20 antibodies; rituximab